Crystallization of Barium Sulfate with Magnesium Chlorite and Calcium Chlorite Additives - Novel Karaman; Susilowati; Gerri Adhit Fachriansyah; Reffi Allifyanto; A. P. Bayuseno (Future Science, 2022)
Barium sulfate scale grew on industrial oil equipment make damaged either in injection or producing wells. A series of experiments were performed to estimate the precipitation rate of barium sulfate in laboratory equipment from brines containing the concentration of barium ions (3500 ppm) and varying concentrations of calcium and magnesium ions (10 and 20 ppm). Additionally, stirring speeds (240 and 480 rpm) affecting the crystallization of barium sulfate scales were also studied through kinetic analysis. At a certain stirring speed, the precipitation of the barium sulfate scale decreased since its solubility increased with increasing concentrations of Ca and Mg-cations, as indicated by changes in constant rate values. All solid crystals obtained from experiments contained mainly pure barite as validated by X-Ray Diffraction (XRD) method. The SEM micrograph for the morphology of barite showed particles with prismatic and tabular-shaped crystals on the order of 2 to 5 µm particles. The kinetic results provided a general reaction rate equation that can predict barium sulfate deposition in the reservoir for a given brine, supersaturation, and time durations of mixing.